An interpretive analysis of the legislators' debates on the reproductive health bill - Tiongco, Beatriz B. (Quezon City Population Institute, University of the Philippines Diliman, 2010)
Using an intrepretive methodology, this paper examines the legislators' framing of the reporductive health (RH) policy issue in order to explore the multiple perspectives, values and beliefs underpinning the legislators' deliberation on the RH bill. The legislators on either side of the RH debate frame the policy issue n reproductive health as a human right issues. For the authors of the RH bill, it address the right to health, but for the opposing legislators, it is an infringement on the right to practice one's religious belief and on the primary right of parents to plan their families. Legislators opposed to the bill view it as a family planning bill that promotes a contraceptive mentality. Consequently, notions that it is mainly about birth control and by extension, population control persists in this group. Moreover, legislators opposing the RH Bill also see it as measure that limits the population size, which in turn is inimical to the country because without a large population, the country would not have the OFWs who keep the economy strong. A point of convergence between the two extreme position of basic services, such as health care and education are necessary to turn human resources into assets for the country. The legislators' debates also reveal the need for legislators to revisit the government's obligations under the International Covenant on Economic, Social and Cultural Rights and related international treaties to respect, protect and fulfill the right to health. Furthermore, policy discussions on the RH bill must also emphasize the complementarity between the human rights framework of the RH bill and human development in order to illuminate the specific pathways by which reproductive health can enhance the well-being of individuals.
Thesis
Includes bibliographical references.
Keywords: Reproductive health -- Law and legislation; Reproductive health